2008
DOI: 10.1080/13803390701380583
|View full text |Cite
|
Sign up to set email alerts
|

A novel task for examining strategic planning: Evidence for impairment in children with ADHD

Abstract: Children with attention deficit hyperactivity disorder (ADHD) often show poor performance on tasks that require strategic planning. To assess this ability, we developed a paper and pencil task that required consistent use of a simple test-taking strategy to maximize the number of points. The visual discrimination task with minimal cognitive demands required children to maximize their gains by responding only to outlined high-point problems and to skip the low-point problems. The task was administered twice, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Moreover, the Behavioral Assessment of the Dysexecutive Syndrome, the Behavior Rating Inventory of Executive Function, and the Tests of Everyday Attention all have child versions that provide developmental norms for studying ecologically valid executive control and enable the researcher to investigate most of the same executive control domains across much of the life span. This does not discount the potential contribution of other measures such as the Multiple Errands Shopping Test (Shallice & Burgess, 1991; Alderman et al, 2003), the Cooking Task (Chevignard et al, 2008), or the Test Taking Strategy Task (Kofman et al, 2008); however, additional research is needed to validate and standardize these measures.…”
Section: Verisimilitude: One Approach To Ecological Validitymentioning
confidence: 99%
“…Moreover, the Behavioral Assessment of the Dysexecutive Syndrome, the Behavior Rating Inventory of Executive Function, and the Tests of Everyday Attention all have child versions that provide developmental norms for studying ecologically valid executive control and enable the researcher to investigate most of the same executive control domains across much of the life span. This does not discount the potential contribution of other measures such as the Multiple Errands Shopping Test (Shallice & Burgess, 1991; Alderman et al, 2003), the Cooking Task (Chevignard et al, 2008), or the Test Taking Strategy Task (Kofman et al, 2008); however, additional research is needed to validate and standardize these measures.…”
Section: Verisimilitude: One Approach To Ecological Validitymentioning
confidence: 99%
“…Unlike previous research that has shown that individuals with ADHD often have difficulty maintaining the used of a strategy (Kofman et al, 2008), students in this study continued to use the planning and writing strategies through the remaining phases of the study. Curtis, Noah, Christian, and Sarah were not only able to use the strategies consistently, but to use them correctly.…”
Section: Srsd and Students With Adhdmentioning
confidence: 51%
“…Finally, Kofman, Larson, and Mostofsky (2008) examined the strategic planning skills of students with ADHD. Students were required to consistently use a simple testtaking strategy to earn points.…”
Section: Adhd Theorymentioning
confidence: 99%
“…The prospective memory task had to be initiated and the child was instructed to switch to all four different tasks at least once. Children with ADHD were less able to remember plans than children without ADHD leading to impaired strategic planning in children with ADHD (Kofman, Larson, & Mostofsky, 2008). Speedy execution of multiple tasks also contributed to frequent errors in children with ADHD (Kliegel, Ropeter, & Mackinlay, 2006).…”
Section: Introductionmentioning
confidence: 99%